(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The detection and tracking of mobile vehicles at current traffic sites is the emerging research area for intelligent transport systems. In this search, we offer a mysterious cellular automated engine model to address the problem of environmental changes associated with the methods and methods of the rear subtraction of dynamic vehicle tracking. The proposed model deals with the fuzzy cellular operator, which has been set up with less vague "exclusive" support rules and "operates as the following mode logic to deal with degrees of uncertainty in the rule of similar operations. In fact/ at each step, the background update is determined according to the number of active cells and the blur mapping function; therefore, mobile compounds that resemble their grey level are simply detected with a grey background. Furthermore, the treatment technique is used on a visual measurement basis to detect the blockage of the vehicle and the breakdown of the vehicle by category of blockage and the results show the experimental method proposed is more robust and accurate than the traditional methods of detecting and tracking vehicles in a timely manner.